Pengaruh Disiplin Kerja Dan Etos Kerja Terhadap Kinerja Karyawan di PT. Fuzi Citra Mandiri - Sukmayadi Sukmayadi; Paroli Paroli; Syaifuddin Syaifuddin (Coopetition : Jurnal Ilmiah Manajemen, 2023)
The essence of the problem in this research is that the performance of employees at PT Fuzi Citra Mandiri has not been optimal. This study aims to determine the effect of work discipline on employee performance, the effect of work ethic on employee performance, the influence of work discipline and work ethic on employee performance at PT. Fuzi Citra Mandiri. This study used a descriptive analytical method with a survey approach, quantitative methods, data collection techniques namely observation and questionnaires. The analysis technique used is multiple regression analysis, correlation test, coefficient of determination and hypothesis testing. The results of the discussion show that the effect of work discipline on employee performance is 96.2%, the effect of work ethic on employee performance is 54.2% and the influence of work discipline and work ethic on employee performance at PT. Fuzi Citra Mandiri is 67.4% and there are still 32.6% other factors. The results of testing the hypothesis that f count = 6.133 and f table = 3.35, the hypothesis which states that simultaneously work discipline and work ethic have an influence on employee performance at PT. Fuzi Citra Mandiri.